2015
DOI: 10.1111/jphp.12404
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of fucosterol isolated from the edible brown algae, Ecklonia stolonifera and Eisenia bicyclis, on tert-butyl hydroperoxide- and tacrine-induced HepG2 cell injury

Abstract: These results suggest that fucosterol may be an effective hepatoprotective agent that could be useful for preventive therapies against oxidative stress-related hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…This insightful paper outlines the approaches necessary for using VCD in the determination of absolute conguration. 537 The rst asymmetric synthesis of (À)-dolastatrienol (14-hydroxydolasta-1(15),7,9-triene) 538 was reported 539 along with a concise synthesis of dictyodendrins A and F. 540 Additionally, there were many papers and reviews dealing with the biological properties of brown algal polyphenolics [541][542][543][544][545][546][547][548][549][550][551][552][553][554][555][556][557] and carotenoids. 15,[558][559][560][561][562] 6 Red algae…”
Section: Brown Algaementioning
confidence: 99%
“…This insightful paper outlines the approaches necessary for using VCD in the determination of absolute conguration. 537 The rst asymmetric synthesis of (À)-dolastatrienol (14-hydroxydolasta-1(15),7,9-triene) 538 was reported 539 along with a concise synthesis of dictyodendrins A and F. 540 Additionally, there were many papers and reviews dealing with the biological properties of brown algal polyphenolics [541][542][543][544][545][546][547][548][549][550][551][552][553][554][555][556][557] and carotenoids. 15,[558][559][560][561][562] 6 Red algae…”
Section: Brown Algaementioning
confidence: 99%
“…A similar study by Chen et al demonstrated that fucosterol isolated from S. fusiforme also enhanced the transactional activity of both LXR‐α and LXR‐β, indicating a selective LXR‐β agonist and a natural cholesterol‐lowering agent. Recently, Choi et al reported that hepatoprotective effect of fucosterol may be due to increase in the hepatic level of glutathione and inhibition of ROS generation as well as increase in the activity of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). These findings suggest that fucosterol could be used for preventive therapies against oxidative stress‐related hepatotoxicity.…”
Section: Biological Effects Of Fucosterolmentioning
confidence: 99%
“…10 The total MeOH (70%) extract and partition fractions from Sargassum angustifolium, Chondria dasyphylla and Ulva flexuosa were evaluated against colon carcinoma (HT-29), colorectal adenocarcinoma (Caco-2), breast ductal carcinoma (T47D) and Swiss mouse embryo fibroblast (NIH 3 T3) cell lines by MTT assay. The hexane fraction from C. dasyphylla (IC 50 The genus Sargassum belongs to the brown algae of class Phaeophyceae, in the order Fucales. Several publications have confirmed that Sargassum metabolites have a wide range of biological activities, including antibiotic, anti-HIV, anticoagulant, anticonvulsant, anti-inflammatory, antineoplastic and antitumor properties.…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…Brown algae is a kind of macroalgae in the ocean. Fucosterol is a sort of algal phytosterol in ethanol extract of brown algae, which has been proved to have multiple biological activities, including antioxidant [14][15][16], anti-inflammatory [17][18][19], anticancer [20], antimicrobial [21], anti-depression [22], etc. Previous research have reported fucosterol on anti-cervical cancer [20], anti-leukemia [23], anti-colorectal cancer [24], etc., but there are few studies on the mechanisms of fucosterol in treating non-small cell lung cancer, and its potential therapeutic targets and related pathways have not been reported in detail.…”
Section: Introductionmentioning
confidence: 99%